Classic ballet and eating disorders - Joseani Paulini Neves Simas; Adriana Coutinho de Azevedo Guimarães (Journal of Physical Education (Maringá), 2008)
Classic ballet with its extreme aesthetic concern can promote eating disorders such as nervous anorexia and bulimia. This review has the purpose of analyzing the eating disorders in classical dancers. Analyzing theoretical references one concludes that several studies have shown an increase in the incidence of eating disorders. The influence of the media and the image of lean woman as the ideal must be considered in the etiology of the eating disorders. In classical ballet the search for perfectionism, high expectation, pressure on the part of the family and instructors and the emotional instability can lead to eating disorders. Studies show that the dance has a negative influence on the corporal image and that ballet classes seem to encourage sliminess beyond normal limits, which may trigger eating disorders.